Experimental and finite element studies of prefabricated timber-concrete composite structures with glued perforated steel plate connections. (1st October 2022) - Tao, Haotian; Shi, Benkai; Yang, Huifeng; Wang, Chaochao; Ling, Xiu; Xu, Jiawei
Highlights: Push-out tests on the glued perforated steel plate connections. Bending tests on the prefabricated timber-concrete composite beams. Three-dimensional finite element analysis on prefabricated timber-concrete composite structures. Abstract: To evaluate the feasibility of adopting glued perforated steel plate (GSP) connections in prefabricated timber-concrete composite (PTCC) structures, two series of tests were conducted in this study: push-out tests on prefabricated GSP (PGSP) connections and bending tests on PTCC beams. The same experimental programmes on cast-in-situ timber-concrete composite (TCC) structures with this type of connection were also performed. For validation, the three-dimensional finite element (FE) models considering the orthotropic elastic–plastic damage behavior of the timber, damage plasticity characteristics of the concrete, fracture of the adhesive, and the nonlinear shear-slip behavior of the connections were developed. The test results demonstrated that the glued perforated steel plate connections have excellent slip stiffness and shearing capacity but low ductility due to the brittle fracture of the adhesive. Owing to the high anchorage performance of the grouting cements and low shrinkage behavior of the dry construction method, the connection stiffness and load-carrying capacity of PGSP are higher than those of GSP. The PTCC beams showed better bending performance than the cast-in-situ TCC beams as a result of the higher slip stiffness of PGSP than that of GSP. Additionally, the FE numerical results are in good agreement with the test results in terms of the failure modes, shear-slip behavior of the connections, and bending performance of the composite beams.